HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI KELURAHAN KUBANG RAYA KECAMATAN SIAK HULU - Yulia Febrianita; Ainil Fitri; Ririn Muthia Z (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Many factors cause stunting in toddlers, but because they are very dependent on the mother/family, the family and environmental conditions that affect the family will have an impact on their nutritional status. Reduced nutritional status occurs due to inadequate nutritional intake and frequent occurrence of infections. So environmental factors, circumstances and family behavior that facilitate infection affect the nutritional status of toddlers. This study aims to determine the relationship between environmental sanitation and the incidence of stunting in children under five in Kubang Raya Village, Siak Hulu District. The design of this study was analytic with a cross-sectional approach. The study looked at the relationship between environmental sanitation and the incidence of stunting. The research was conducted in Kubang Raya Village, Siak Hulu District. The population in this study were mothers who had toddlers totaling 66 people. The data were collected using a questionnaire and the analysis was carried out using SPSS. The results of the study found that there was a relationship between latrine ownership and stunting with p value = 0.005, there was a relationship between trash can ownership and stunting with p value 0.006, there was no relationship between the availability of SPAL and stunting with p value 0.814, and there was a relationship between the availability of clean water and the incidence of stunting. stunting with p value 0.005 Keywords: Environmental Sanitation, Stunting, Toddler